Effect of Chemical Treatments on the Shelf Life of Rambutans (Nephelium lappaceum) - II - Mohamed, Suhaila; Othman, Eshah; Abdullah, Fauziah (1988)
Dipping rambutans for 5 minutes in sodium metabisulphite, calcium chloride and metabisulphite or calcium chloride and ascorbic acid solutions helped reduce %unacceptable fruits by up to 30% when fruits were stored packaged at 8 C Chemical dipping of rambutans and sulfur dioxide treatments were found to be less effective in prolonging the shelf life compared to low temperature storage. Techniques which slow down respiration rate and dehydration rate- were found to be more effective in prolonging the shelf life of rambutans than methods to inhibit enzymic browning. Fruits treated with sodium metabisulphite + calcium chloride in PE at 8 C with soaking time of 5-10 minutes, remained sweet and firm on the 17th day. Shelf life of treated fruits stored at room temperature is not significantly different from untreated fruits.